2024
DOI: 10.26599/fshw.2022.9250016
|View full text |Cite
|
Sign up to set email alerts
|

Higher intakes of lysine, threonine and valine are inversely associated with non-alcoholic fatty liver disease risk: a community-based case-control study in the Chinese elderly

Abstract: The associations of branched chain amino acids (BCAAs), aromatic amino acids (AAAs) and essential amino acids with non-alcoholic fatty liver disease (NAFLD) risk have been widely investigated. However, the individual amino acid associated with NAFLD risk remained inconclusive. The present study aimed to investigate the associations between individual amino acid intake and NAFLD risk in the Chinese elderly.Methods: A community-based health check-up program was conducted from Mar. to Nov. 2020 in Qingdao, China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…It is reported that supplements of threonine for mice in a high-fat diet alleviated the onset of fat deposition ( 59 ). Of note, a community-based case-control study including senior Chinese aged over 65 years has showed that threonine, valine and lysine were negatively correlated with NAFLD risk and highlighted the potential beneficial effect of the increased consumption of food rich in those essential amino acids as eggs, milk and deep-sea fish ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that supplements of threonine for mice in a high-fat diet alleviated the onset of fat deposition ( 59 ). Of note, a community-based case-control study including senior Chinese aged over 65 years has showed that threonine, valine and lysine were negatively correlated with NAFLD risk and highlighted the potential beneficial effect of the increased consumption of food rich in those essential amino acids as eggs, milk and deep-sea fish ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Threonine prevents fatty buildup in the liver and is one of the aminodetoxifiers. Li et al [ 33 ] found, in a community-based case-control study, that the consumption of lysine-, threonine-, and valine-rich foods helps to reduce nonalcoholic fatty liver disease risk in the elderly population.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, glutamic acid concentration was found to be altered in NAFLD, probably due to its involvement in glutathione formation and possibly connected to the severity of NAFLD [ 14 ]. It was recently found that greater threonine intake was inversely associated with NAFLD risk in elderly Chinese people [ 36 ]. In contrast, the current study found that higher plasma threonine concentrations were associated with higher MRI-cT1.…”
Section: Discussionmentioning
confidence: 99%